AGRONOMIC STUDY OF PANICUM SARMENTOSUM ON OPEN DRYLAND AGROECOSYSTEMS IN PALU VALLEY: The effect of different defoliation intervals on several forage production parameters - Andi Lagaligo Amar; Tarsono Tarsono; Kaharudin Kasim; Mulyati Mulyati; Mustaring Mustaring (AGROLAND The Agricultural Sciences Journal (e-Journal), 2022)
The study aimed to compare several production parameters of Panicum sarmentosum at different defoliation intervals whose its benefit can add knowledge about the favorable defoliation interval of grasses as a feed forage source. The agronomic study was done in plot experiments comparing parameters such as number of tillers, percentage of flowering clumps, forage dry-matter (DM) content, forage DM production, and leaf:stem ratio as an effect of 3 defoliation interval treatments, namely; 4, 5, and 6 weeks with 3 repetitions. The effect of treatment on parameters was determined by the analysis of variance. Significant parameters affected by treatment were then further tested to determine the best defoliation interval between treatments by using the least significancy difference test. The results showed that the number of tillers, the percentage of forage DM content, the production of stem DM (kg/ha) and the leaves stems ratio were not affected by the defoliation interval. Defoliation interval significantly (P<0.05) affected the number (%) of flowering clumps, the production of forage biomass (kgDM/ha), and the production of leaf DM (kgDM/ha) of Panicum sarmentosum Roxb. grass. The one-year observation obtained on the productivity of Panicum sarmentosum Roxb. has not reflected the survivability and productivity of this type of superior local forage yet.